PRICE FLUCTUATIONS AND ELASTICITY OF COFFEE PRICE TRANSMISSION IN THE WORLD AND DOMESTIC COFFEE MARKETS OF NORTH SUMATRA PROVINCE - Sihotang, Jusmer; Purba, Martin Luter; Nopeline, Nancy; Lastri, Lastri (STABN RADEN WIJAYA WONOGIRI, 2024)
The research aims to analyze fluctuation Coffee prices in North Sumatra Province and districts selected ( Taput, Simalungun, Karo, and Dairi ), analyzing elasticity of coffee price transmission from the world coffee market to the coffee market in Sumatra Province, and analyzing elasticity of coffee price transmission between the North Sumatra Province market and Taput, Simalungun, Karo, and Dairi Regencies. Research data is secondary data series time 2012-2023, with tool analysis coefficient of variation and elasticity transmission price.Research findings show that coffee prices in North Sumatra Province and West Sumatra Regency Taput, Simalungun, Karo, and Dairi are very volatile and include in category fluctuation high price.The elasticity of coffee price transmission between the world market and the North Sumatra Province market is inelastic. Changes the price of arabica and robusta coffee on the world market is only cause change very small coffee prices in North Sumatra Province. This show market system yet efficient that can happen Because adjustment costs in the supply chain or the abuse of market power in oligopsony market structures by exporters or traders in the world market.The elasticity of Arabica coffee price transmission in Taput and Karo Districts is elastic, where the percentage change Arabica coffee prices in both regency the more big compared to with percentage change coffee prices in North Sumatra Province. This show existence market structure that is oligopoly, so that coffee producers in both regency be in position strong bargaining position in determine price. However, the elasticity of the transmission of Arabica and Robusta coffee prices in the Regency Simalungun and Robusta coffee in the Regency nature inelastic, where percentage change prices on both regency more small than percentage change coffee prices in North Sumatra Province. This show existence market structure that is monopsony in both regency so that can cause market abuse occurs power by intermediary traders in controlling prices in Simalungun Regency and Dairi Regency.